Numerical hemolysis performance evaluation of a rotary blood pump under different speed modulation profiles - Huang, Feng; Lei, Huan; Ying, Shunv; Fu, Yang; Li, Qipeng; Ruan, Xiaodong (Frontiers in Physiology, 2023)
Speed modulation methods have been studied and even used clinically to create extra pulsation in the blood circulatory system with the assistance of a continuous flow rotary blood pump. However, fast speed variation may also increase hemolysis potential inside the pump. This study investigates the hemolysis performance of a ventricular assist rotary blood pump under sinusoidal, square, and triangular wave speed modulation profiles using the computational fluid dynamics (CFD) method. The CFD boundary pressure conditions of the blood pump were obtained by combined simulations with the pump’s mathematical model and a complete lumped parameter cardiovascular model. The hemolysis performance of the blood pump was quantified by a hemolysis index (HI) calculated from a Eulerian scalar transport equation. The HI results when the blood pump run under three speed profiles were obtained and compared with the constant speed condition. It reveals that speed modulations will slightly affect the pump hemolysis, and the hemolysis differences between different speed modulation profiles are non-obvious. This study suggests that speed modulation could be a feasible way to improve the flow pulsatility of rotary blood pumps while not increasing the hemolysis.